Prometastatic secretome trafficking via exosomes initiates pancreatic cancer pulmonary metastasis. (1st July 2020) - Ogawa, Kosuke; Lin, Qiushi; Li, Le; Bai, Xuewei; Chen, Xuesong; Chen, Hua; Kong, Rui; Wang, Yongwei; Zhu, Hong; He, Fuliang; Xu, Qinggang; Liu, Lianxin; et al.
Abstract: To demonstrate multifaceted contribution of aspartate β-hydroxylase (ASPH) to pancreatic ductal adenocarcinoma (PDAC) pathogenesis, in vitro metastasis assay and patient derived xenograft (PDX) murine models were established. ASPH propagates aggressive phenotypes characterized by enhanced epithelial-mesenchymal transition (EMT), 2-D/3-D invasion, extracellular matrix (ECM) degradation/remodeling, angiogenesis, stemness, transendothelial migration and metastatic colonization/outgrowth at distant sites. Mechanistically, ASPH activates Notch cascade through direct physical interactions with Notch1/JAGs and ADAMs. The ASPH-Notch axis enables prometastatic secretome trafficking via exosomes, subsequently initiates MMPs mediated ECM degradation/remodeling as an effector for invasiveness. Consequently, ASPH fosters primary tumor development and pulmonary metastasis in PDX models, which was blocked by a newly developed small molecule inhibitor (SMI) specifically against ASPH's β-hydroxylase activity. Clinically, ASPH is silenced in normal pancreas, progressively upregulated from pre-malignant lesions to invasive/advanced stage PDAC. Relatively high levels of ASPH-Notch network components independently/jointly predict curtailed overall survival (OS) in PDAC patients (log-rank test, Ps < 0.001; Cox proportional hazards regression, P < 0.001). Therefore, ASPH-Notch axis is essential for propagating multiple-steps of metastasis and predicts prognosis of PDAC patients. A specific SMI targeting ASPH offers a novel therapeutic approach to substantially retard PDAC development/progression. Highlights: ASPH is silenced in normal pancreas, upregulated in premalignant lesions and pancreatic cancer. ASPH activates Notch cascade to propagate multi-step metastasis. ASPH guides exosomes secretion as a prometastatic outlet. ASPH-driven tumor progression is blocked by specific SMIs against β-hydroxylase activity.